Explaining the collapse of communism in Poland : how the strategic misperception of Round Table negotiators produced an unanticipated outcome - Hayden, Jacqueline P. (Trinity College (Dublin, Ireland). Department of Political Science, 2002)
This dissertation set out to discover why the Polish communist party (PUWP) lost power in Poland over the summer of 1989. Given the fact that neither the PUWP nor Solidarity expected the fall of communism at the outset of the Round Table process, the question to be addressed is what factors best explain the collapse of the party’s hegemony so shortly after its negotiators had concluded a deal they hoped would enable the government to carry out its economic reform programme. The question is an important one because, prior to the collection of data, it was intuitively apparent that PUWP negotiators appeared to have adopted positions and strategies during the Round Table process that led to sub-optimal institutional outcomes for the party. So if it is assumed that the PUWP were rational actors and did not deliberately decide to hand power over to the Solidarity-led opposition, what explains the behaviour and strategic choices that brought about the collapse of the party’s power?
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin